2007
DOI: 10.1086/523353
|View full text |Cite
|
Sign up to set email alerts
|

Contact Binaries with Additional Components. III. A Search Using Adaptive Optics

Abstract: We present results of the Canada-France-Hawaii Telescope adaptive optics (AO) search for companions of a homogeneous group of contact binary stars, as a contribution to our attempts to prove the hypothesis that these binaries require a third star to become as close as observed. In addition to directly discovering companions at separations of !1 00 , we introduced a new method of AO image analysis utilizing distortions of the AO diffraction ring pattern at separations of 0.07 00 Y1 00 . Very close companions, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 25 publications
8
75
1
Order By: Relevance
“…Note that Qian et al (2004) suggest a closer companion to the binary may be causing a variation in the light curve with a period of ∼25 yr. However, no close companion was identified by Rucinski et al (2007), and our companion is too wide to introduce such a short period variation.…”
Section: Hip 115819 (Vz Piscium)mentioning
confidence: 77%
See 1 more Smart Citation
“…Note that Qian et al (2004) suggest a closer companion to the binary may be causing a variation in the light curve with a period of ∼25 yr. However, no close companion was identified by Rucinski et al (2007), and our companion is too wide to introduce such a short period variation.…”
Section: Hip 115819 (Vz Piscium)mentioning
confidence: 77%
“…As angular momentum transfer to additional components can tighten an inner binary and lead to contact, Rucinski et al (2007) observed VZ Piscium as part of an adaptive optics search for companions to contact binaries. We have identified an M8 companion at a separation of 30 .…”
Section: Hip 115819 (Vz Piscium)mentioning
confidence: 99%
“…Yang & Liu (2003) considered both mass exchange and mass loss mechanisms that could cause the observed decrease in the period but found that the cyclic variation superimposed on the decreasing trend was quasi-periodic; hence, it could only be attributed to magnetic activity. Pribulla & Rucinski (2006) and Rucinski et al (2007) did not detect the signature of a third body in their studies dedicated to detecting faint third bodies in contact binary systems. In addition, broadening functions constructed for radial velocity analysis by Pribulla et al (2009a) did not show any evidence of a third companion in the system.…”
Section: Rw Commentioning
confidence: 97%
“…D 'Angelo et al (2006) analyzed 4000 spectra from 75 close binaries for spectroscopic signature of tertiaries and identified 23 triple systems (almost one third). Rucinski et al (2007) presented the results of a search for TC of a group of contact binaries and concluded that the presence of a close component is a very common phenomenon for very close binaries with orbital period , 1 day.…”
Section: Introductionmentioning
confidence: 99%